Vasorelaxant and Antispasmodic Effects of Some Polyphenols and Glycoside in Rat Smooth Muscles - Shekha, Mudhir S. (Science Journal of University of Zakho, 2014)
Objective: The present study was undertaken to investigate the effect of Luteolin, chlorogenic acid, amygdalin and tannic acid on vascular smooth muscle contractility.Materials and Methods: The effect of different concentrations of some polyphenols and glycosides on contractile responses of isolated aorta, ileum and trachea to Acetylcholine, KCl and phenylephrine (PE) were evaluated.Results: The results of the current study indicated that luteolin and chlorogenic acid has potent relaxant effects on KCl and PE-induced contractions in rat’s aortic ring. Amygdalin and tannic acid reduced ACh-induced ileum contractions significantly. Conclusions: The inhibitory effect of luteolin and chlorogenic acid on the contraction induced by PE and KCl may be due to their anti-adrenergic and anti-hyperpolarizing effect.
Keywords: vasorelaxant; antispasmodic; polyphenol; glycoside; rat; smooth muscles